Analisis Peluang Guessing pada Culture Fair Intelligence Test (Cfit) 3A dengan Metode IRT - Medianta Tarigan; Fadillah Fadillah (Jurnal Ilmu Perilaku, 2021)
Culture Fair Intelligence Test (CFIT) is a popular nonverbal intelligence measuring instrument used for psychological examination purposes. The figural form of a test with multiple choice as in CFIT can increase the chances of guessing behavior performed by the test subject. Guessing behavior will increase when subjects are encouraged to work on as many uncertain questions as possible whether they know the answer to the question. This behavior can affect the validity of test results in distinguishing quality and under-qualified test subjects. Until now, research related to CFIT psychometric properties is still limited. This study aims to evaluate the validity of CFIT by analyzing the guessing behavior using the Item Response Theory (IRT) method. The sample of this study was 1,955 participants and the results showed that based on IRT 3 PL modeling, the items in the CFIT 3A are still feasible to use. However, CFIT 3A contains items with an unacceptable guessing rate, 12% of the total number of items. The result of model fit test using Confirmatory Factor Analysis (CFA) method as an additional analysis shows that validity construct of CFIT 3A is good. It is expected that the results of the study can provide up-to-date information on the quality of CFIT 3A items and become a reference for other relevant research in the future.